Determinan Gross Domestic Product Dan Angka Harapan Hidup Terhadap Indeks Pembangunan Manusia: Studi Komparasi Antara Afghanistan Dan China Priode 1990 – 2021 - Agafirdus Ervandus Blutuk; Decci Sandriyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The human development index is a benchmark for determining human welfare in a country. The human development index can be measured by various factors. In this study, the benchmarks used were gross domestic product and life expectancy after birth in Afghanistan and China for the period 1990 to 2021. This benchmark can be seen through the correlation test, where the results show an 80.35% relationship between the human development index and GDP. Meanwhile, the relationship between the human development index and life expectancy after birth was 97.07%. Then, to determine that the data was valid, the researcher used several regression analyses tests. With the regression analysis, researchers can see a comparison of human development in the two countries. Keywords: Human Development Index; Gross Domestic Product; Life Expectancy.